The formation and shape transformation mechanism of a triangular Au nanoplate revealed by liquid-cell TEM. Issue 38 (23rd September 2020) - Jin, Biao; Wang, Haifeng; Sushko, Maria L.; Jin, Chuanhong; Tang, Ruikang
Abstract : Direct liquid-cell TEM investigations highlight the significance of thermodynamics and kinetics during the formation and growth of a Au triangular nanoplate. Abstract : We report two different formation mechanisms of a triangular Au nanoplate through the transformation of a truncated octahedron and the direct formation of a triangular seed using liquid-cell TEM. This work stresses the great significance of thermodynamics and kinetics in the formation and later shape transformation of a triangular nanoplate.